Simulação de um terminal de transporte urbano operando com ônibus elétrico híbrido: avaliação do consumo de energia e estratégias de recarga - Souza, Gustavo Rodrigues de (2021)
Recently, the replacement of fossil fuel energy matrix for clean energy has received great attention in public transport. Several Brazilian cities have provided resources for the acquisition of electric or hybrid electric buses whose battery recharge can be made by an external source (plug-in). In this context, there is a great challenge in evaluating energy consumption and establishing strategies for recharging buses. In this dissertation, a simulation model from the literature for the operation of a hybrid-electric bus is used to evaluate the energy consumption of the bus from a given driving cycle. A driving cycle is determined by a speed profile during the journey taken by the bus. From GPS data acquired during the movement of buses in the public transport of Curitiba, a speed profile is built for different bus lines of Pinheirinho terminal. About 5,500 driving cycles are then obtained for buses of 21 lines of the terminal. The objective is to simulate the electric energy consumption of buses and obtain the State of Charge (SOC) of the batteries for each bus returning to the terminal. Based on this information, another (discrete event) simulation model was developed to simulate the operation of Pinheirinho terminal in Curitiba, by replacing buses of 11 bus lines of the terminal by hybrid electric ones. In the discrete event simulation, a charging station installed inside the terminal allows recharging batteries of the hybrid electric buses. Two scenarios of battery recharge are evaluated when buses enter the terminal: i) SOC below 30%; ii) opportunity recharge, when SOC is between 30-50% and the bus stop time at the terminal is greater than 10 min. The results show that the performance indicators for scenario 2 are slightly better than for scenario 1. The performance indicators are: average recharge time, average waiting time for recharge, average time spent in the terminal and size of the queue generated by using the charging station. In particular, scenario 2 is able to better distribute recharges throughout the day, reducing the length of the charging station queue at certain times of the day.